(untitled) (XXI Century. Spanish Literature and Culture, 2007)
This article explores the consumerist culture adopted by the protagonists of Histories of Kronen, by José Ángel Mañas, as a form of escape and resistance from the norms of a society that does not offer any possibility of a future. The characters of this novel present an attitude of constant defiance with the intention of anesthetizing themselves against the alienation of the exterior world, of moving away from reality, and of hiding the profound loneliness in which they find themselves. They resort to drugs, sex, and alternative music as catalysts of their frustration with the culture of theabsurd and as a form of facing the disillusionment that characterizes the epoch in which they live. Through their integration in a consumerist subculture, they get to be owners of their actions and have true control over some aspect of their existence that consciously moves them further away from the established social prescription.